Representações da metrópole na poesia de T. S. Eliot e Hart Crane (ArtCultura, 2008)
A partir da leitura de À ponte do Brooklyn (1930), de Hart Crane, e de A terra desolada (1922), de T. S. Eliot, pretende-sefazer uma aproximação entre esses dois poemas de modo a evidenciar a representação da cidade moderna e, sobretudo, a relação estabelecida entre o artista e o espaço da metrópole.PALAVRAS-CHAVE: representação, metrópole, poesia moderna.ABSTRACTStarting from the reading of The bridge(1930), of Hart Crane, and of The wast land (1922), of T. S. Eliot, it intends to do an approach among those two way poems to evidence the representation of the modern city and, above all, the established relationship between the artist and the space of the metropolis. KEYWORDS: representation, metropolis, modern poetry.